The quantification of damages for disability and non–material damages in the Civil and Commercial Code of the Nation (about five years from the beginning of its validity) (Nueva Epoca, 2020)
The article reviews some of the interpretive problems generated with the entry into force of Articles 1741 and 1746 of the Civil and Commercial Code of the Argentine Nation.
Keywords: quantification of damages; legal arguments; disability; non material damages; legal interests